Marine and inland fishes of St. Croix, U. S. Virgin Islands: an annotated checklist - Smith-Vaniz, William F.; Jelks, Howard L. (Zootaxa, 2014)
An historical account is given for the ichthyological research at St. Croix, U. S. Virgin Islands, followed by an annotated list of 544 species of mostly marine shore fishes known or reported from the island to depths of 200 m. Color photographs are included for 103 of these species. Collections made at Buck Island Reef National Monument with the ichthyocide rotenone in 2001 and 2005 increased the known ichthyofauna by about 80 species. The rational for inclusion of each species in the checklist is given, with remarks for those species for which additional documentation or voucher specimens are needed. Reports of species known or presumed to have been based on misidentifications are discussed. Of the total marine fish fauna of the island, 404 species (75%) are restricted to the western Atlantic Ocean, (223 of these species are essentially Caribbean endemics that do not occur south of the Amazon River outflow), and no St. Croix endemic species are known. An additional 17 species (3.2%) also occur at mid-Atlantic islands, 57 species (10.6 %) are limited to both sides of the Atlantic Ocean, and 40 species (7.4%) have circumtropical distributions. The four most species-rich families are the Gobiidae (47 species), Serranidae (groupers and sea basses, 41), Labridae (wrasses and parrotfishes, 31), and Labrisomidae (scaly blennies, 27). Literature reports of Mosquitofish, Gambusia sp., from St. Croix apparently were based on misidentifications of a different introduced poeciliid genus. Four species of the amphidromus goby genus Sicydium occur in St. Croix inland waters, together with three established introduced species (one cichlid and two poeciliids). Also included are one catfish (Ictaluridae) and three sunfishes (Centrarchidae) known only from ponds. The Lionfish, Pterois volitans, the only introduced marine species, was first reported from St. Croix in 2008 and is now common despite control efforts.